PENGARUH HARGA, PROMOSI, DAN KEMUDAHAN PENGGUNAAN APLIKASI TERHADAP KEPUTUSAN PEMBELIAN DENGAN MINAT BELI SEBAGAI VARIABEL INTERVENING DI PASARNOW - Nafisyatul, Natasya; Sitorus, Guston; Noviarti (Jurnal Satya Mandiri Manajemen dan Bisnis, 2023)
This research aims to explore the impact of price, promotion, and app usability on purchasing decisions through buying interest as an intervening variable on Pasarnow. The study involves 217 Pasarnow customer respondents, and data is collected through a questionnaire. The analysis utilizes path analysis as a quantitative technique with SPSS 22 & AMOS 24. Findings reveal that the price directly and significantly influences buying interest, as does promotion and app usage ease. Price directly but insignificantly affects purchase decisions. Promotion has no direct impact on purchase decisions, while app usage ease directly and significantly affects them. Buying interest also directly and significantly influences purchase decisions. Additionally, price has an indirect and insignificant effect on purchase decisions through buying interest, similar to promotion and app usage ease.